Proyecto de apoyo a los docentes de la Unidad Educativa Madre de la divina gracia en el desarrollo de actividades de aprendizaje basadas en la teoría del neuroaprendizaje - Peralta Ortega, Jorge Andrés (2017)
The Project of Support to the Teachers of the "Unidad Educativa Madre de la Divina Gracia" in the Development of Learning Activities based on the theory of the Neurolearning proposed a work of psychological intervention through the attention in the Department of Student Counseling of the Educational Unit proposing, from Neurolearning, classroom activities for all school years in joint work with the main actors of this process are the teachers strengthening their work and supporting them in their innovation in the classroom. The participating teachers were 35 between basic and high school with a very important active participation of each of them in the processes of support and training such as workshops, tutorials, conferences and case studies, and crystallized this process in a satisfaction survey at the end of the process in order to know what was learned and to evaluate in projection for subsequent school years in the Educational Unit. The results of work were very well accepted by teachers and evidenced in the classroom, all supported by teamwork with a vice-rector, an important actor and strategic ally with which was evaluated in the internal processes of the institution.